Effect of Adding Ticagrelor to Standard Aspirin on Saphenous Vein Graft Patency in Patients Undergoing Coronary Artery Bypass Grafting (POPular CABG): A Randomized, Double-Blind, Placebo-Controlled Trial. Issue 19 (10th November 2020) - Willemsen, Laura M.; Janssen, Paul W.A.; Peper, Joyce; Soliman-Hamad, Mohamed A.; van Straten, Albert H.M.; Klein, Patrick; Hackeng, Chris M.; Sonker, Uday; Bekker, Margreet W.A.; von Birgelen, Clemens; Brouwer, Marc A.; van der Harst, Pim; et al.
Abstract : Background: Approximately 15% of saphenous vein grafts (SVGs) occlude during the first year after coronary artery bypass graft surgery (CABG) despite aspirin use. The POPular CABG trial (The Effect of Ticagrelor on Saphenous Vein Graft Patency in Patients Undergoing Coronary Artery Bypass Grafting Surgery) investigated whether ticagrelor added to standard aspirin improves SVG patency at 1 year after CABG. Methods: In this investigator-initiated, randomized, double-blind, placebo-controlled, multicenter trial, patients with ≥1 SVGs were randomly assigned (1:1) after CABG to ticagrelor or placebo added to standard aspirin (80 mg or 100 mg). The primary outcome was SVG occlusion at 1 year, assessed with coronary computed tomography angiography, in all patients that had primary outcome imaging available. A generalized estimating equation model was used to perform the primary analysis per SVG. The secondary outcome was 1-year SVG failure, which was a composite of SVG occlusion, SVG revascularization, myocardial infarction in myocardial territory supplied by a SVG, or sudden death. Results: Among 499 randomly assigned patients, the mean age was 67.9±8.3 years, 87.1% were male, the indication for CABG was acute coronary syndrome in 31.3%, and 95.2% of procedures used cardiopulmonary bypass. Primary outcome imaging was available in 220 patients in the ticagrelor group and 223 patients in the placebo group. The SVG occlusion rate in the ticagrelor group was 10.5% (51 of 484 SVGs) versus 9.1% in the placebo group (43 of 470 SVGs), odds ratio, 1.29 [95% CI, 0.73–2.30]; P =0.38. SVG failure occurred in 35 (14.2%) patients in the ticagrelor group versus 29 (11.6%) patients in the placebo group (odds ratio, 1.22 [95% CI, 0.72–2.05]). Conclusions: In this randomized, placebo-controlled trial, the addition of ticagrelor to standard aspirin did not reduce SVG occlusion at 1 year after CABG. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02352402. Abstract : Supplemental Digital Content is available in the text.